Acute Myocardial Infarction: Experience at a Teaching Hospital - Khurram, Muhammad; Khaar, Hamama-tul-Bushra; Javed, Saima; Hasan, Zubair; Goraya, M Fayaz; Haq, Usman Ul (Journal of Rawalpindi Medical College, 2026)
Background: To note patient characteristics, risk factors, use of streptokinase, complications, and mortality in subjects presenting with acute myocardial infarction. Methods: This prospective, observational, case study was conducted at DHQ Teaching Hospital, Rawalpindi, from January 2001 to January 2002. All 95 patients who were admitted with a diagnosis of acute myocardial infarction during this period were included. Patients were managed in the standard way, initially in CCU and then in the medical ward. Data obtained was statistically examined using Epi Info 2000. Results: Of the 95 patients, 70 (73.7%) were male and 25 (26.3%) female. Mean patient age was $57±12.54$ years. Anterior wall was involved commonly (38.9% patients). Forty-nine (51.6%) patients received thrombolysis with streptokinase. Arrythmias (57.9% patients) and cardiac failure (53.6% patients) were the commonest complications of acute myocardial infarction. Mean hospital stay was 8 days. 11.5% $(n=11)$ patients died during hospital stay, of these 27.2% $(n=3)$ received streptokinase. Age, sex, smoking, and sedentary life styles were common (>50%) risk factors for myocardial infarction. Conclusion: Acute myocardial infarction is common in males and over the age of 50 years. Majority of these patients are candidates for thrombolytic therapy with streptokinase. Myocardial infarction related in-hospital mortality, even in a tertiary care setting, may be 11.5%